The reshaping of urban structure in South Africa through municipal capital investment: evidence from three municipalities - Laldaparsad, Sharthi; Geyer, Herman; Du Plessis, Danie (Department of Urban and Regional Planning, University of the Free State, 2013)
Although Spatial Development Frameworks are regarded as the key spatial restructuring tool of local municipalities, the investment of public resources through the municipal capital budget is of equal importance. Public-sector capital investment plays a key role in the reorientation of spatial priorities by guiding private investment and restructuring historically inefficient spaces. The alignment of spatial development strategies and municipal capital budgets provide a potentially effective restructuring mechanism for local municipalities. This article analyses the degree of alignment of these instruments through the case-study investigation of three local municipalities: Johannesburg, Cape Town, and Rustenburg. The findings indicate that spatial development frameworks significantly influence budgetary capital spending patterns and address growth management and connectivity. However significant resources were committed in marginalised fragmented settlements, a trend that reinforced spatial inefficiencies.

Alhoewel Ruimtelike Ontwikkelingsraamwerke as die belangrikste plaaslike ruimtelike herstrukturering instrument beskou word, is die investering van openbare hulpbronne deur middel van die munisipale kapitale begroting ewe belangrik. Die investering van kapitale uitgawes in die openbare sektor speel ’n belangrike rol in die ordening van ruimtelike prioriteite deur histories ondoeltreffende ruimtes te herstruktureer en private sektor beleggings te oriënteer. Die belyning van die ruimtelike ontwikkelingstrategieë en munisipale kapitale begrotings bied ’n potensiële doeltreffende herstruktureringmeganisme vir plaaslike munisipaliteite. Hierdie artikel ontleed die graad van belyning tussen hierdie instrumente deur ŉ gevallestudie-ondersoek in drie munisipaliteite: Johannesburg, Kaapstad, en Rustenburg. Die bevindings toon aan dat ruimtelike ontwikkelingsraamwerke die kapitaalbestedingpatrone wel sterk beïnvloed het en die bestuur van stedelike groei en ruimtelike skakeling aangespreek het. ŉ Beduidende gedeelte van hulpbronne is egter ook in gemarginaliseerde en gefragmenteerde nedersettings belê, ŉ tendens wat ondoeltreffende ruimtelike patrone bevorder het.

Le ha tsela tsa mosebetsi oa tswelopele ea morero oa dibaka di bonoa e le tsona tse bohlokoa hore dibaka di reroe hantle ho masepala, chelete ea ho sebeletsa sechaba ke masepala le eona e bohlokoa. Chelete ea ho sebeletsa sechaba e bapala karolo e kholo diqetong tsa ho hore na sebaka se reroa joang. Lenane la bohlokoa ba hore na ho hloka ho rereloa eng sebakeng se feng le chelete e behilong ke masepala e beheloa ho rerela sebaka, ke tsona tse thusang hore masepala ho sebetse ka mokhoa oo phethahetseng. Serapa sena se shebisana le tsamaiso mmoho ea dintlha tsena e ipapisitse le bo masepala ba bararo e leng ba Johannesburg, Cape Town le Rustenburg. Diphumano tsa chebisiso ena di bontshitse tsela tsa mosebetsi oa tswelopele ea merero ea dibaka e ama pokello le karolo ea chelete. Le ha ho le joalo ditlhoko tse khethehileng di tsamaisitsoe ho dibaka tse ne di di hloka haholo. E e leng ea baka hore merero ea dibaka e se ke ea sebetsa hantle ho tloha moo.
Keywords: Spatial development framework; Municipalities